Baptism Well dedicated to Joseph Baptista - Mumbai Archive Project Team (Jio Institute, 2024)
Our Lady of the Rosary baptism well is dedicated to Joseph Baptista, who was born in Matharpacady, on January 4, 1864. Baptista was a fervent nationalist who studied law to qualify as a barrister. He was an Indian National Congress (INC) member who, via his writings, speeches, and political engagement, significantly contributed to the mobilisation of public opinion in support of Indian Home Rule.